Accuracy of CA 19-9 and Radiologic Imaging in Detecting Recurrence After Resection for Pancreatic Cancer - Sperti, Cosimo; Beltrame, Valentina; Bissoli, Sergio; Pedrazzoli, Sergio (JOP. Journal of the Pancreas, 2013)
No abstract available. Image: Pancreatic cancer cell.